Pemberian Remisi Sebagai Upaya Penanganan Over Kapasitas Di Rutan Kelas I Jakarta Pusat - Suci, Putri Wulan; Ritonga, Raja (VIVA THEMIS, 2024)
Remission is one of the supporting legal means that provides influence in realizing the goals of the correctional system. Considering that currently the Class I Detention Center in Central Jakarta is experiencing a number of inmates that exceeds capacity or is over capacity. Of course, granting remissions to prisoners will be one of the efforts to reduce overcapacity in prisons or detention centers. So the aim of this research is to describe how granting remissions can help reduce the current overcapacity in Class I Detention Centers in Central Jakarta. The research used is qualitative research with the type of field research. Primary research data was collected through observation, interviews and documentation. Secondary data was collected through literature study. Next, all the found data were analyzed descriptively. The research results show that granting remissions can reduce the sentence but remissions have not been able to reduce overcapacity. Apart from that, there are still several obstacles in granting remission to prisoners even though the provisions have been regulated in Law no. 22 of 2022 concerning Corrections. Among the obstacles found were related to the completeness of prisoner administration and the behavioral factors of the prisoners themselves.